Forward backward correlations in pp and p-Pb collisions using the TPC at ALICE - Passad,Martin (2016)
This thesis reports on the use of \(ν_{dyn}\) to investigate the ridge structure in p-p and p-Pb collisions using the ALICE detector at LHC. The conclusions drawn in this thesis is that there is nothing which indicates long range correlations, but that the multiplicity dependence of forward-backward correlations measured using \(ν_{dyn}\) is dominated by an increase in the local contribution from jet production.